DIGITALIZATION, ARTIFICIAL INTELLIGENCE AND WORK FORCE - Jovevski, Dimitar; Sasho, Josimovski (Institute for Knowledge Management, 2022)
Digitalization has been changing organizations from the time when Internet was discover. On the other side digitalization is rapidly reshaping our workplaces. Nowadays people cannot imagine business or their personal lives without digital technologies, digital technologies often change individual’s work and collective work practices in significant but unpredictable ways. Digitalization has created many challenges at companies and also at work place, but also create excellent opportunities for organizations. New technologies are a key driver of labor market change in recent decades. On the other side there are technological developments in areas such as artificial intelligence and concerns that this technologies will destroy jobs. There are lot of existing studies which examined the role of digitalization on business performance and worker productivity. Digital technologies help but also allow companies to improve their workplace form traditional/outdated to fresh and digital. The benefits from the digitalization are appeal to both employees and management. In general technologies are unpopular among workers in traditional companies, primarily because they are not well known, as well as because of the fear of possible job losses. A large number of surveys and surveys of the opinion of workers reveal a small percentage of workers who support the implementation of robotic production systems because most believe that they will "take" their jobs. For that reason, in recent years, the issue of informing workers with new technologies that work with artificial intelligence has been updated, in order to neutralize the fear of the unknown. Artificial intelligence is being perfected to ensure complementarity of production processes to improve productivity and, ultimately, increase profits. Those jobs that will be closed and replaced by robotization and the introduction of artificial intelligence will actually generate new jobs that should be filled with workers through their retraining and retraining , because machines and artificial intelligence still need to be managed by a human factor. In this paper we will explore the situation about the level of digitalization, implementation of AI (artificial intelligence) in different fields of working and how this process cultivate the digital work force, what are the skills of workers' representatives for information management, digitalization, AI (artificial intelligence) management, as well as the creation of a personnel strategy and its implementation in the company.
Keywords: artificial intelligence, work force, digitalization